Importance of CEO attention in influencing incumbent responses to disruptive innovation - Heesun Gha; Min Young Kim; Hyeon Jin Ro; Seungho Choi (Administrative Sciences, 2023)
This study investigates incumbent firm responses to disruptive innovation in the rapidly evolving South Korean retail industry. The study explores the factors behind an incumbent firm's decision-making processes when responding to disruptive innovation and examines the reasons behind varied incumbent responses. It investigates the agents that influence a firm's decision by conducting the qualitative case study of a South Korean retail giant, Lotte. By collecting archival data from various sources, this paper was able to analyze different interviews and statements of the chief executive officer (CEO). From the analysis, it was determined that the firm's overall actions were aligned with the CEO's assertions. Thus, this paper asserts that Lotte's response to disruptive innovation was directly influenced by the CEO's attention. The results of this study further add to the discourse of disruptive innovation by highlighting the importance of CEO discretion in deciding a firm's direction and by further emphasizing the relationship between managerial leadership and innovation.
Keywords: 350; CEO attention; disruptive innovation; e-commerce; incumbent response; retail